2000
DOI: 10.1001/archinte.160.15.2297
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Significant Relationships Between Aggregation of Major Coronary Risk Factors and the Acceleration of Carotid Atherosclerosis in the General Population of a Japanese City

Abstract: Background: Carotid arterial intimal-medial thickness (IMT) measured by high-resolution B-mode ultrasonography has come to be used as a noninvasive surrogate end point to measure progression of atherosclerosis. However, there are no detailed data on the relationship between aggregation of coronary risk factors and carotid atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…Yamasaki et al have reported that predictors of increasing carotid IMT in Japanese patients with type 2 diabetes were a baseline IMT and average HbA1c level (20). Mannami et al have reported that IMT increases in the presence of hypertension or hyperlipidemia (21). In this study, the IMT was greatest in the isolated home hypertension in the morning group.…”
Section: Blood Pressure and Target Organ Damagesupporting
confidence: 51%
“…Yamasaki et al have reported that predictors of increasing carotid IMT in Japanese patients with type 2 diabetes were a baseline IMT and average HbA1c level (20). Mannami et al have reported that IMT increases in the presence of hypertension or hyperlipidemia (21). In this study, the IMT was greatest in the isolated home hypertension in the morning group.…”
Section: Blood Pressure and Target Organ Damagesupporting
confidence: 51%
“…The study population of the Suita Study was based on samples randomly selected from 12,200 Japanese residents of Suita [20][21][22] . The participants had been visiting the National Cerebral and Cardiovascular Center every 2 years since 1989 for regular health checkups.…”
Section: Study Populationmentioning
confidence: 99%
“…Studies on the variability of platelet responsiveness to agonists have been mainly performed in the Caucasian population; studies in the Asian population are very limited. Since 1989, we have conducted the Suita Study, an epidemiological study of cerebrovascular and cardiovascular diseases, in a general urban population cohort in Japan [20][21][22] . The present study was undertaken to clarify the factors influencing the interindividual variability of platelet responsiveness to agonists in a Japanese urban general population.…”
Section: Introductionmentioning
confidence: 99%
“…The carotid artery intima-media thickness (CIMT) is the best known sonographic marker for early atherosclerotic vascular wall lesions (18). Previous cross-sectional studies in different populations have shown that, increase in CIMT is associated with cardiovascular event prevalence (19)(20)(21)(22)(23)(24)(25). Additionally, CIMT increase was strongly and significantly correlated with myocardial infarction and stroke incidence (26).…”
mentioning
confidence: 99%
“…It has been shown that a direct relation exits between CIMT and clinical cardiovascular disease (19)(20)(21)(22). Due to these data, CIMT assessment can be used to document regression or progression of atherosclerosis (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) Besides, at least two large epidemiologic studies proposed that increased CIMT values are associated prospectively with increased risk of coronary artery disease (24,25,37). Several studies, CIMT was significantly increased in SCF patients.…”
mentioning
confidence: 99%